2020
DOI: 10.3390/jpm11010002
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin as a Potential Prognostic Marker for Sepsis According to Actual Practice Guidelines

Abstract: The 2016 Surviving Sepsis Campaign guidelines define sepsis as life-threatening organ dysfunction caused by a dysregulated host response to infection. This study had the objective of assessing the efficacy of presepsin in the prognosis of sepsis. This was a single-center prospective study, performed in Craiova Emergency Hospital, that included 114 patients admitted in the Intensive Care Unit (ICU) department between 2018 and 2019 fulfilling the sepsis criteria. Including criteria were: age ≥ 18, sepsis diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
4
18
0
3
Order By: Relevance
“…Similar to our results, Behnes et al, found significant correlations between PS and PCT, as well as SOFA and APACHE scores, and subsequently severity of the disease [30]. In accordance with these findings, Drăgoescu et al, identified significant correlations between PS and the SOFA score and CRP [31]. Aliu-Bejtaa et al, revealed a strong correlation of PS with SOFA score, thus letting them believe that PS might be a specific sepsis biomarker [24].…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our results, Behnes et al, found significant correlations between PS and PCT, as well as SOFA and APACHE scores, and subsequently severity of the disease [30]. In accordance with these findings, Drăgoescu et al, identified significant correlations between PS and the SOFA score and CRP [31]. Aliu-Bejtaa et al, revealed a strong correlation of PS with SOFA score, thus letting them believe that PS might be a specific sepsis biomarker [24].…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis found a mortality rate of 4% [ 10 ]. Our case also met the 2001 criteria of sepsis [ 11 , 12 , 13 ].…”
Section: Discussionsupporting
confidence: 53%
“…There are authors who consider that a negative serological test does not rule out the diagnosis of anthrax if there is a characteristic clinical picture in a suggestive epidemiological context [ 8 , 18 ]. The absence of seroconversion was observed due to early treatment during infection, even in bacteriologically confirmed cases [ 8 , 12 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%